3-x+2=1

Simple and best practice solution for 3-x+2=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-x+2=1 equation:


Simplifying
3 + -1x + 2 = 1

Reorder the terms:
3 + 2 + -1x = 1

Combine like terms: 3 + 2 = 5
5 + -1x = 1

Solving
5 + -1x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -1x = 1 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 1 + -5
-1x = 1 + -5

Combine like terms: 1 + -5 = -4
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4

See similar equations:

| p^2=20p | | 58+9x=-62+3x | | 4(3a+2)-6=-22 | | 7(1+a)=-4a-26 | | (d+9)(d+6)=-2 | | 4(2x-3+2-5x)= | | -16+5x=4y | | 3-2(x+7)= | | -11*5a=6(5a+4) | | z=12+y | | 6y+7-3y+6= | | -2x^2+2x+40=0 | | 2p(p-7)=0 | | 7.4+2=p-2.8 | | 7x-19+19=8+19 | | 5=-4(h+4) | | 3x^2-y^2+30x+78=0 | | -6*f+13=2*f-11 | | 21=-7w | | -100=-4x-4(2x-8) | | 2=3g-4 | | 106=x-42 | | f(2)-6=2(4)+3 | | 12b+7=31 | | -6(r+4)=-8r-18 | | 2r^2-8r-10=0 | | -4(9s-7)=35+5s | | Y-6=8+3 | | 5+3x=x+5+2x | | 7(R-11)-6r= | | Y=(8x+3)(x-8) | | -2p+7=14+1+4p+4 |

Equations solver categories